Muscling up the heart: a preadolescent cardiomyocyte proliferation spurt contributes to heart growth - Zhang, Cheng-Hai (2014)
A recent study from Naqvi et al in Cell shows that in mice during preadolescence, cardiomyocytes undergo a burst of proliferation that is related to a thyroid hormone surge. This study challenges the conventional model of the timing of terminal differentiation and provides a direction for further mechanistic research on cardiomyocyte proliferation and differentiation.